Iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation as well as preparation method and application of iron-cobalt-zirconium catalyst

By preparing iron-cobalt zirconium catalysts, the stability and activity of the catalyst are improved by using zirconium elements, the problem of insufficient catalyst activity and stability in the prior art is solved, and efficient carbon dioxide hydrogenation reaction is achieved, and the selectivity and yield of low-carbon olefins and liquid hydrocarbons are improved.

CN119500136AActive Publication Date: 2025-02-25ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411468121.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-25
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

In the prior art, in the process of hydrogenating carbon dioxide to produce low-carbon olefins and liquid hydrocarbons, there are challenges in the activity, selectivity, stability and cost of catalysts, making it difficult to achieve large-scale industrial production.

Method used

Iron-cobalt zirconium catalyst is prepared by co-precipitation, hydrothermal synthesis, drying and calcination, and zirconium elements are added to improve the structural stability and electronic properties of the catalyst.

Benefits of technology

It significantly improves the conversion of carbon dioxide, inhibits side reactions, improves the selectivity of low-carbon olefins and liquid hydrocarbons, and has high catalyst stability and relatively economical cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500136A_ABST
    Figure CN119500136A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation, a preparation method of the iron-cobalt-zirconium catalyst and application of the iron-cobalt-zirconium catalyst to preparation of liquid hydrocarbon and co-production of low-carbon olefin through carbon dioxide hydrogenation. The catalyst is prepared by taking nitrate of iron, nitrate of cobalt and nitrate of zirconium as raw materials through operations of coprecipitation, hydrothermal synthesis, drying, roasting and the like. By adopting the technology, the invention provides the carbon dioxide hydrogenation catalyst and limits the preparation method of the carbon dioxide hydrogenation catalyst. The preparation method is simple, and the obtained catalyst has high activity, high liquid hydrocarbon selectivity and low-carbon olefin selectivity at the temperature of 280 DEG C, is good in stability, relatively economical and practical, and has a good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to an iron-cobalt-zirconium catalyst suitable for catalyzing the hydrogenation of carbon dioxide to produce liquid hydrocarbons and co-producing light olefins, as well as a preparation method and application thereof. Background Art

[0002] In the context of global climate change and energy transformation, the conversion and utilization of carbon dioxide has become a hot topic of scientific and industrial concern. As a major greenhouse gas, the huge amount of carbon dioxide emissions has had a significant impact on the global climate system. Therefore, exploring efficient conversion pathways for carbon dioxide, especially converting it into high-value-added chemicals such as low-carbon olefins (ethylene, propylene, butene) and liquid hydrocarbons (gasoline, diesel, etc.), is of great significance for achieving the recycling of carbon resources, alleviating the energy crisis and responding to climate change.

[0003] At present, research on the production of low-carbon olefins and liquid hydrocarbons from carbon dioxide has made significant progress. Through chemical conversion methods such as catalytic hydrogenation, carbon dioxide can be converted into low-carbon olefins and liquid hydrocarbons under certain conditions. This process not only realizes the resource utilization of carbon dioxide, but also promotes the development of green chemistry and sustainable energy. However, the current technology still faces challenges in catalyst activity, selectivity, stability and cost, which require further research and optimization.

[0004] Chinese patent CN 117282463 A provides a method for preparing a composite catalyst for producing high value-added liquid fuel by hydrogenating carbon dioxide. By introducing one or more molecular sieves to adjust the shell catalyst composition of the capsule catalyst, the directional synthesis of the product is further improved. This type of catalyst has a high selectivity for liquid hydrocarbons at 300°C, but the carbon dioxide conversion rate is relatively low, and the preparation process of the physical coating coupled catalyst is relatively inconvenient, which is not conducive to industrial large-scale production. Chinese patent CN108421547 B provides a carbon dioxide hydrogenation catalyst for oil production with high selectivity for low-carbon olefins and liquid hydrocarbons at low temperature (250°C), but the carbon dioxide conversion rate is not high, and the additive is Pd, which is relatively costly. Chinese patent CN 112570031A proposes a high-carbon hydrocarbon catalyst prepared by using an Fe-based metal organic framework as a precursor and impregnating additives (Zn, K, Na, Mn, etc.). The carbon dioxide conversion rate reaches 37.87% at 340°C, and the liquid hydrocarbon selectivity reaches 83.78%. However, the metal additive components impregnated in the catalyst are prone to agglomeration, which is not conducive to the uniform dispersion of the metal components, and the catalyst stability is poor.

[0005] In order to realize the large-scale industrial application of catalytic hydrogenation of carbon dioxide, it is necessary to develop catalysts with simple and practical preparation methods, easy industrial production, good reproducibility and high efficiency, so as to improve the carbon dioxide conversion rate while increasing the yield of high value-added products - low-carbon olefins and liquid hydrocarbons. Summary of the invention

[0006] In view of the above-mentioned technical problems existing in the prior art, the purpose of the present invention is to provide an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation and a preparation method and application thereof. The prepared iron-cobalt-zirconium catalyst can be used for carbon dioxide hydrogenation to produce liquid hydrocarbons and light olefins and other related reactions. The catalyst has the advantages of good carbon dioxide hydrogenation activity, high product selectivity and good stability.

[0007] The present invention provides a method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation, and the specific steps are as follows: Step S1, dissolving ferric nitrate nonahydrate, cobalt nitrate hexahydrate and zirconium nitrate pentahydrate in deionized water, and stirring at room temperature to obtain a uniformly mixed solution; Step S2, adding alkaline solution dropwise into the above mixed uniform solution, heating in a water bath and stirring continuously; in this step, the nitrate solution reacts with the alkaline solution to generate hydroxide precipitate; Step S3, transferring the suspension after stirring to a reactor and placing it in an oven for heating reaction; in this step, a hydrothermal reaction occurs, the solute in the solution in the reactor gradually reaches a supersaturated state, and crystals begin to grow on suitable crystal nuclei.

[0008] Step S4, cooling, centrifuging, washing and drying the suspension after the reaction to obtain a catalyst precursor; in this step, the purpose of cooling, centrifuging and washing is to remove excess sodium ions; and the purpose of drying is mainly to remove water.

[0009] Step S5, calcining the catalyst precursor to obtain an iron-cobalt-zirconium catalyst. In this step, the purpose of calcination is to make the crystal structure and crystal phase of the catalyst more stable so that sintering will not occur due to heat at the reaction temperature.

[0010] As an improvement, in step S1, the molar ratio of ferric nitrate nonahydrate, cobalt nitrate hexahydrate and zirconium nitrate pentahydrate is 100:20-70:0.5-20; preferably 100:45-55:1-10.

[0011] As an improvement, in step S2, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution or a mixed solution of sodium hydroxide and potassium hydroxide, preferably a sodium hydroxide solution. The molar ratio of the alkaline solution to ferric nitrate nonahydrate is 4-8:1, preferably 4.5-5.5:1.

[0012] As an improvement, in step S2, the water bath heating temperature is 40-90°C for 0.3-2 h, preferably 55-65°C for 0.5-1.5 h.

[0013] As an improvement, in step S3, the temperature of the oven is 120-200°C, the reaction time is 10-24 h, preferably 175-185°C, and the heating time is preferably 12-15 h.

[0014] As an improvement, in step S4, the washing times are 2 or more, preferably 3 times. The drying temperature is 60-100°C, the drying time is 12-24 hours, preferably 75-85°C for 13-15 hours.

[0015] As an improvement, in step S5, the calcination is to place the precursor in a muffle furnace, in an air atmosphere, and calcine at 350-500°C for 3-6 hours, with a heating rate of 2-10°C / min. Preferably, calcination is performed at 400-450°C for 3.5-4.5 hours, with a heating rate of 2.5-5°C / min.

[0016] In the catalyst prepared by the present invention, iron is the main active species in the carbon dioxide hydrogenation reaction, that is, iron can convert carbon dioxide into carbon monoxide. Highly dispersed cobalt can effectively convert carbon monoxide attached to the iron surface into hydrocarbons through Fischer-Tropsch synthesis, and iron has a strong chain growth ability in Fischer-Tropsch synthesis to generate long-chain hydrocarbons. As an auxiliary agent, the addition of zirconium can enhance the structural stability and electronic properties of the catalyst, prevent the catalyst from sintering and agglomeration during the reaction, thereby improving the activity and stability of the catalyst.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The iron-cobalt-zirconium catalyst disclosed in the present invention has a very significant effect on improving the carbon dioxide hydrogenation activity when the zirconium element added is at a very low content; (2) The iron-cobalt-zirconium catalyst disclosed in the present invention has good stability. At a temperature of 280°C, the single-pass conversion rate of carbon dioxide can reach more than 40%, the total selectivity of light olefins and liquid hydrocarbons in the product can reach more than 70%, and the yield of light olefins and liquid hydrocarbons can reach 30%.

[0018] The catalyst of the present invention is prepared by coprecipitation, hydrothermal synthesis, drying and calcination with iron nitrate, cobalt nitrate and zirconium nitrate as raw materials. The catalyst prepared by the present invention significantly improves the carbon dioxide conversion rate at a temperature of 280°C, inhibits the occurrence of side reactions, and improves the selectivity of low-carbon olefins and liquid hydrocarbons. The catalyst preparation method is simple and practical, can maintain excellent performance under various reaction conditions, is not easy to deactivate, and has high stability. The catalyst does not contain precious metal elements, involves common reagents, and is relatively economical. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The XRD spectra of the catalysts of Examples 1, 2, 3, 4, 5 and Comparative Example 1 of the present invention are shown.

[0020] Figure 2 Graph showing the carbon dioxide hydrogenation performance of the catalysts of Examples 1, 2, 3, 4, 5, 6, 7, 8 of the present invention and Comparative Example 1.

[0021] Figure 3 It is a graph showing the carbon dioxide hydrogenation performance of the catalysts of Example 3 of the present invention and Comparative Examples 2, 3, 4, 5, and 6. DETAILED DESCRIPTION

[0022] The invention is introduced below in conjunction with specific embodiments. It should be pointed out that the embodiments only describe the preparation process of the catalyst within a certain range. Without departing from the technical premise of the present invention, other researchers can make multiple modifications to the present invention, and these modifications should also be regarded as within the scope of protection of the present invention. Example 1

[0023] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.0004 mol of zirconium nitrate pentahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as Catalyst 1. Example 2

[0024] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.002 mol of zirconium nitrate pentahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as Catalyst 2. Example 3

[0025] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.004 mol of zirconium nitrate pentahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as Catalyst 3. Example 4

[0026] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.006 mol of zirconium nitrate pentahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as Catalyst 4. Example 5

[0027] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.008 mol of zirconium nitrate pentahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as Catalyst 5. Example 6

[0028] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.004 mol of zirconium nitrate pentahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 185°C for 15 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as Catalyst 6. Example 7

[0029] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.004 mol of zirconium nitrate pentahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 75°C for 15 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as Catalyst 7. Example 8

[0030] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.004 mol of zirconium nitrate pentahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 500 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as Catalyst 8. Comparative Example 1

[0031] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate and 0.02 mol of cobalt nitrate hexahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as reference catalyst 1. Comparative Example 2

[0032] (1) Dissolve 0.04 mol ferric nitrate nonahydrate, 0.02 mol cobalt nitrate hexahydrate, and 0.004 mol calcium nitrate tetrahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as reference catalyst 2. Comparative Example 3

[0033] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.02 mol of cobalt nitrate hexahydrate, and 0.004 mol of zinc nitrate hexahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as reference catalyst 3. Comparative Example 4

[0034] (1) Dissolve 0.04 mol ferric nitrate nonahydrate, 0.02 mol cobalt nitrate hexahydrate, and 0.004 mol copper nitrate trihydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as reference catalyst 4. Comparative Example 5

[0035] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.016 mol of cobalt nitrate hexahydrate, and 0.004 mol of zirconium nitrate hexahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as reference catalyst 5. Comparative Example 6

[0036] (1) Dissolve 0.04 mol of ferric nitrate nonahydrate, 0.024 mol of cobalt nitrate hexahydrate, and 0.004 mol of zirconium nitrate hexahydrate in 50 mL of deionized water and stir at room temperature to obtain a uniform mixed solution; (2) Add 50 mL of 4 mol / L sodium hydroxide solution dropwise to the mixed solution and stir continuously in a 60°C water bath for 1 h. (3) The stirred suspension was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated in an oven at 180°C for 14 h. (4) After the reaction is completed, the reactor is cooled to room temperature, the product is obtained by centrifugation, and then washed three times with 300 mL of deionized water. The precipitate obtained by washing is transferred to a beaker and placed in an oven at 80°C for 14 h to obtain a catalyst precursor; (5) The catalyst precursor was placed in a muffle furnace and calcined at 400 °C for 4 h in an atmosphere of normal pressure and air at a heating rate of 2.5 °C / min to obtain a black powder. The powder was pressed into tablets, crushed and sieved to obtain the desired granular catalyst, which was recorded as reference catalyst 6.

[0037] The above catalysts were tested for carbon dioxide hydrogenation reaction performance under the same reaction conditions. The specific reaction conditions were as follows: 0.5 g of catalyst was mixed with 1.5 g of quartz sand and loaded into a fixed bed reactor, reduced in pure H2 gas at 350°C and atmospheric pressure for 5 h, and then reacted in a mixed gas of CO2:N2:H2=23:8:69 (volume ratio) at 280°C, 2.0 MPa, and 50 mL / min for 24 hours, and the products were analyzed by a gas chromatograph equipped with a thermal conductivity detector (TCD) and a hydrogen flame ionization detector (FID). The reaction performance test results of the catalyst are shown in Table 1.

[0038] Table 1 Carbon dioxide hydrogenation performance on different catalysts catalyst Carbon dioxide conversion rate (%) Selectivity of light olefins (%) Liquid hydrocarbon selectivity (%) Yield of light olefins and liquid hydrocarbons (%) Example 1 38.42 26.84 50.05 29.54 Example 2 41.05 24.35 48.27 29.81 Example 3 43.89 22.09 48.18 30.84 Example 4 44.83 20.96 40.15 27.40 Example 5 45.28 13.45 39.29 23.88 Example 6 43.96 22.01 48.06 30.80 Example 7 43.64 22.23 47.36 30.37 Example 8 44.53 21.34 47.12 30.49 Comparative Example 1 32.89 23.15 48.92 23.70 Comparative Example 2 54.44 0.26 16.62 9.19 Comparative Example 3 33.77 22.17 52.14 25.09 Comparative Example 4 21.51 11.73 55.96 12.04 Comparative Example 5 43.14 23.16 43.01 28.55 Comparative Example 6 44.21 20.81 45.58 29.35 Figure 1 The XRD spectra of the catalysts of Examples 1, 2, 3, 4, 5 and Comparative Example 1 are shown in FIG. As can be seen from the figure, the main object of the sample is cobalt ferrite, and the phase of zirconium dioxide is detected only when the zirconium content is high, which may be due to the high dispersion of low-content zirconium in the cobalt ferrite.

[0039] Figure 2The carbon dioxide hydrogenation performance diagram of the catalysts of Examples 1, 2, 3, 4, 5, 6, 7, 8 and Comparative Example 1 of the present invention. It can be seen from the figure combined with Table 1 that with the increase of zirconium content, the carbon dioxide conversion rate continues to increase, the selectivity of light olefins and liquid hydrocarbons continues to decrease, and the yield of light olefins and liquid hydrocarbons shows a trend of first increasing and then decreasing. It shows that the addition of zirconium element has a very obvious effect on the carbon dioxide hydrogenation activity of cobalt ferrite catalyst, but with the increase of zirconium content, the selectivity of the target product is suppressed. When the Fe / Co / Zr molar ratio is 100 / 50 / 10, the yield of the target product is the highest, at which time the carbon dioxide conversion rate is 43.89%, and the sum of the selectivity of light olefins and liquid hydrocarbons reaches 70.27%. The difference between Comparative Example 1 and the catalysts of Examples 1, 2, 3, 4, and 5 is that no zirconium element is added to Comparative Example 1. Its carbon dioxide conversion rate is lower than that of any catalyst with added zirconium element, indicating that zirconium element can improve the activity of the catalyst at an extremely low content. The difference between Examples 6, 7, and 8 and Example 3 is that the raw materials used are the same, but the conditions in the preparation process are slightly different. The hydrothermal condition of Example 6 is 185°C for 15 h, the drying condition of Example 7 is 75°C for 15 h, and the calcination condition of Example 8 is 500°C for 4 h. Slightly changing the preparation conditions has little effect on the catalyst, and the activity and yield are almost unchanged.

[0040] Figure 3 The carbon dioxide hydrogenation performance diagram of the catalysts of Example 3 of the present invention and Comparative Examples 2, 3, 4, 5, and 6. The difference between Comparative Examples 2, 3, and 4 and Example 3 is that zirconium is replaced by other elements of the same content. Comparative Example 2 adds calcium, and the carbon dioxide conversion rate is significantly improved, but the target product selectivity is very low and the yield is very low; Comparative Example 3 adds zinc, and the target product selectivity is high, but the carbon dioxide conversion rate is not high, resulting in low yield; Comparative Example 4 adds copper, and the target product selectivity is not high, and the carbon dioxide conversion rate is not high, and the yield is very low. The difference between Comparative Examples 5 and 6 and Example 3 is that the cobalt content in the catalyst is different. The molar ratio of iron, cobalt, and zirconium in Comparative Example 5 is 100:40:10, Comparative Example 6 is 100:60:10, and Example 3 is 100:50:10. It can be found that the target product selectivity of Comparative Examples 5 and 6 is lower than that of Example 3, and the yield of the target product is lower than that of Example 3.

[0041] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation, characterized in that: The process steps include: S1: dissolving ferric nitrate nonahydrate, cobalt nitrate hexahydrate and zirconium nitrate pentahydrate in deionized water, and stirring at room temperature to obtain a uniform mixed solution; S2: Add alkaline solution drop by drop into the above mixed solution, heat in a water bath and stir continuously; S3: transferring the stirred suspension to a reactor and placing it in an oven for heating and reaction; S4: cooling, centrifuging, washing and drying the suspension after the reaction to obtain a catalyst precursor; S5: calcining the catalyst precursor to obtain an iron-cobalt-zirconium catalyst.

2. The method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation according to claim 1, characterized in that: In step S1, the molar ratio of ferric nitrate nonahydrate, cobalt nitrate hexahydrate and zirconium nitrate pentahydrate is 100:20-70:0.5-20; preferably 100:45-55:1-10.

3. The method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation according to claim 1, characterized in that: In step S2, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution or a mixed solution of sodium hydroxide and potassium hydroxide, preferably a sodium hydroxide solution.

4. The method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation according to claim 1, characterized in that: In step S2, the molar ratio of the alkaline solution to ferric nitrate nonahydrate is 4-8:1, preferably 4.5-5.5:

1.

5. The method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation according to claim 1, characterized in that: In step S2, the water bath is heated at a temperature of 40-90° C. for 0.3-2 h, preferably at 55-65° C. for 0.5-1.5 h.

6. The method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation according to claim 1, characterized in that: In step S3, the temperature of the oven is 120-200° C., the reaction time is 10-24 h, preferably 175-185° C., and the heating time is preferably 12-15 h.

7. The method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation according to claim 1, characterized in that: In step S4, the washing times are 2 or more, preferably 3 times; the drying temperature is 60-100° C., the drying time is 12-24 h, preferably 75-85° C. for 13-15 h.

8. The method for preparing an iron-cobalt-zirconium catalyst suitable for carbon dioxide hydrogenation according to claim 1, characterized in that: In step S5, the calcination is performed by placing the precursor in a muffle furnace, and calcining at 350-500° C. for 3-6 h in an air atmosphere, with a heating rate of 2-10° C. / min, preferably calcining at 400-450° C. for 3.5-4.5 h, with a heating rate of 2.5-5° C. / min.

9. An iron-cobalt-zirconium catalyst suitable for hydrogenation of carbon dioxide, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. Use of the iron-cobalt-zirconium catalyst as claimed in claim 9 in catalytic hydrogenation of carbon dioxide to produce liquid hydrocarbons and co-production of light olefins.

Citation Information

Patent Citations

  • A catalyst for carbon dioxide hydrogenation to oil production, its preparation method and application

    CN108421547B

  • Catalyst suitable for preparing high-carbon hydrocarbon through carbon dioxide hydrogenation and preparation and application thereof

    CN112570031A

  • Preparation method for preparing high-added-value liquid fuel composite catalyst through carbon dioxide hydrogenation

    CN117282463A

  • Iron-cobalt-potassium-loading zirconium dioxide catalyst, preparation method and applications thereof

    CN110871075A

  • Method for synthesizing low-carbon olefin through carbon dioxide hydrogenation by adopting iron-based catalyst

    CN112169799A

Cited By

  • Iron-based catalyst for preparing olefin from carbon dioxide as well as preparation method and application of iron-based catalyst

    CN120115154A

  • An oxide medium material for preparing high-purity hydrogen from semi-coke tail gas and a preparation method thereof

    CN121338760B